Use of non-hyperaccumulator plant species for the phytoextraction of heavy metals using chelating agents (Scientia Agricola, 2013)
Soil contamination by heavy metals is a challenge faced by many countries, and engineering technologies to solve this problem are expensive and can cause negative impacts on the environment. One way to minimise the levels of heavy metals in the soil is to use plants that can absorb and accumulate heavy metals into harvestable parts, a process called phytoextraction. Typical plant species used in research involving phytoextraction are heavy metal hyperaccumulators, but plants from this group are not good biomass producers and grow more slowly than most species; thus, they have an important role in helping scientists understand the mechanisms involved in accumulating high amounts of heavy metals without developing symptoms or dying. However, because of their slow growth, it is not practical to use these species for phytoextraction. An alternative approach is to use non-hyperaccumulator plants assisted by chelating agents, which may improve the ability of plants to accumulate more heavy metals than they would naturally. Chelating agents can be synthetic or organic acids, and the advantages and disadvantages of their use in improving the phytoextraction potential of non-hyperaccumulator plants are discussed in this article. We hope to draw attention to ways to improve the phytoextraction potential of non-hyperaccumulator plants that produce a large amount of biomass and to stimulate more research on phytoextraction-inducing substances.